Effects of Pre- and Post-Exercise Cold-Water Immersion Therapy on Passive Muscle Stiffness - Hüttel, Moritz; Golditz, Tobias; Mayer, Isabel; Heiss, Rafael; Lutter, Christoph; Hoppe, Matthias Wilhelm; Engelhardt, Martin; Grim, Casper; Seehaus, Frank; Forst, Raimund; Hotfiel, Thilo (Sportverletzung · Sportschaden, 2020)
Background Cold-water immersion (CWI) has become a popular preventive, regenerative and performance-enhancing intervention in various sports. However, its effects on soft tissue, including changes of intramuscular stiffness, are poorly understood. The purpose of this study was to investigate the effect of CWI on muscle stiffness.Patients/Material and Methods Thirty healthy participants were included and divided into the three following groups (n = 10): 1) post-ESU group: exercise and CWI (post-exercise set-up); 2) control group: exercise without CWI (control condition); 3) pre-ESU group: CWI alone (pre-exercise set-up). Acoustic radiation force impulse (ARFI) elastography was conducted to assess tissue stiffness (shear wave velocity, SWV). Values obtained at resting conditions (baseline, t0) were compared to values post-exercise (t1, for post-ESU group and control group), post-CWI (t2, for post-ESU group and pre-ESU group; rest for control group) and to 60-min follow-up time (t3, for all groups). Data were assessed in superficial and deep muscle tissue (rectus femoris muscle, RF; vastus intermedius muscle, VI).Results For the post-ESU group (CWI post-exercise), there was no significant difference between the time points of measurements: exercise (t1: RF: 1.63 m/s; VI: 1.54 m/s), CWI (t2: RF: 1.63 m/s; VI: 1.53 m/s) and at 60-min follow-up (t3: RF: 1.72 m/s; VI: 1.61 m/s). In the control group, a significant decrease of SWV was found between baseline conditions at t0 and post-exercise (t1) at VI (VI: 1.37 m/s; p = 0.004; RF: 1.59 m/s; p = 0.084). For t2 and t3, no further significant changes were detected. Regarding the pre-exercise set-up (pre-ESU group), a significant decrease in SWV from baseline to t2 in VI (1.60 m/s to 1.49 m/s; VI: p = 0.027) was found.Conclusion This study shows varying influences of CWI on muscle stiffness. Overall, we did not detect any significant effects of CWI on muscle stiffness post-exercise. Muscle stiffness-related effects of CWI differ in the context of a pre- or post-exercise condition and have to be considered in the implementation of CWI to ensure its potential preventive and regenerative benefits.
Keywords: recovery; regeneration; CWI; DOMS; EIMD; musculoskeletal ultrasound; sonography; elastography